(untitled) (Baghdad Science Journal, 2011)
This paper presents the design, construction and investigates an experimental study of a parabolic Trough Solar Collector (PTSC). It is constructed of multi – piece glass mirror to form the parabolic reflector (1.8 m ? 2.8 m) its form were checked with help of a laser and carbon steel rectangular as receiver. Sun tracker has been developed (using two – axis) to track solar PTSC according to the direction of beam propagation of solar radiation. Using synthetic oil as a heat transfer its capability to heat transfer and load high temperature (?400 oc). The storage tank is fabricated with stainless steel of size 50 L. The experimental tests have been carried out in Baghdad climatic conditions (33.3o N, 44.4o E) during selective days of the months October and November. The performance of PTSC is evaluated using outdoor experimental measurements including the useful heat gain, the thermal instantaneous efficiency and the energy gained by the storage tank oil. The storage tank oil temperature is increased from 30oc at 9:30h to 136oc at 13:30h without draw – off oil. The experimental result shows the average thermal efficiency was 42% which is fairly acceptable assessment results of a PTSC locally.